An analysis of 2,480 space-occupying lesions of the orbit from 1976 to 2011 - Bonavolontà, Giulio; Strianese, Diego; Grassi, Piergiacomo; Comune, Chiara; Tranfa, Fausto; Uccello, Giovanni; Iuliano, Adriana (Ophthalmic plastic and reconstructive surgery, 2013)
To evaluate the frequencies of orbital space-occupying lesions seen at single orbital unit in a period of 35 years. In this retrospective case series, the authors reviewed the medical records of 2,480 consecutive patients referred to the authors' Orbital Unit for evaluation of an orbital mass between 1976 and 2011. The final diagnosis in each case was established by a combination of history, ocular findings, diagnostic imaging, and histopathologic analysis, when available. The number and percentage of benign and malignant tumors were determinated, also according to the age of the patients and the tumor location within the orbit. This study adhered to the principles of the Declaration of Helsinki. Of the 2,480 lesions, 1,697 (68%) were benign and 783 (32%) were malignant. The most frequent benign tumors were dermoid cyst (14%) and cavernous hemangioma (9%). The most common malignant tumors were non-Hodgkin lymphoma (12%), basal cell carcinoma (3%), and orbital metastases (3%). In patients younger than 60 years, benign tumors are more frequent, whereas in patients older than 60 years, the frequency of malignant tumors increased. Regarding the distribution in the orbit, the most common tumors were dermoid cyst (206 cases) in the upper-outer quadrant, mucocele (155 cases) in the upper-inner quadrant, basal cell epithelioma (35 cases) in the lower-inner quadrant, cavernous hemangioma (68 cases) in the lower-outer quadrant, and meningioma (90 cases) in central space. Most of the tumors were located in the upper-outer quadrant. In the lower-inner quadrant, malignant tumors were more frequent than benign tumors. The authors' findings highlight the distinctive nature of the orbital oncology experience at an ocular oncology department.